THE EFFECTIVENESS OF LITERACY MAPPING ON STUDENTS’ READING NARRATIVE TEXT - Zauzah Muthiah; Muhammad Sofian Hadi; Mutiarani (Getsempena English Education Journal, 2021)
The objective of this research is to decrease students' reading narrative text and effectiveness their reading level using literacy mapping students' from 8G of SMP Negeri 18 Depok. This study used a Quantitative Method with a Pre-Experimental design by implementing the design of pre-test and post-test. In this study, the writer used one class as the sample with a total of the students' are 30 students'. The data were collected by giving pre-test and post-test as the instrument. The result of the study was calculated using a t-test. The findings showed that the students' post-test scores (were was higher than pre-test scores. By using the t-test, the result of the t-table with degrees of freedom (df) 0.01 obtained 2.048. The findings reveal that these research successes to decrease students' reading narrative text and effectiveness their reading level using literacy mapping.